Love Expression Found In Breaking Dawn Movie By Stephenie Meyer: Pragmatics Analysis - Hikmawati, Irma Candra, Prof. Dr. Endang Fauziati, M.Hum, Siti Fatimah, S.Pd. M.Hum (2013)
Her research aims at clarifying the pragmalinguistic forms of love expressions, clarifying the speaker intentions of love utterance, describing the speech acts of love expression used in Breaking Dawn movie. The type of the research is descriptive qualitative research. The object of this research is love expressions used in Breaking Dawn (Romance film) directed by Stephenie Meyer. The data of this research are sentences containing love expressions found in Breaking Dawn movie by Stephenie Meyer. The researcher finds 28 love expressions in Breaking Dawn movie by Stephenie Meyer. This movie contains many dialogues especially love expressions. The method of collecting data in this research are watching the original Movie Breaking Dawn movie by Stephenie Meyer, finding out love expressions in Breaking Dawn movie by Stephenie Meyer, note talking all the expression in Breaking Dawn movie by Stephenie Meyer, identifying the pragmalinguistic forms of love expressions used in the movie, and re-typing all the sentence containing love expression in the movie. The writer uses descriptive interpretive to analyze the data of love expression in this movie. The techniques of analysis are finding out love expressions in Breaking Dawn movie by Stephenie Meyer, clarifying the pragmalinguistic forms in love expression, clarifying the speaking intentions in love expression, and describing the speech acts found in love expression in this movie. The result of the study has three findings. First, the pragmalinguistic forms of the love are word and sentences (positive imperative, declaration, interrogative, and exclamatory sentence). in pragmalinguistic form, the researcher finds the types of love, they are romance, affection, and friendship form. Second, the researcher finds speaker intention. They are fear of loosing, showing attention, showing affection, complementing, expectation, happiness, feel a pity, jealous, scared of being, and convince the bride. Third, the speech act of love utterance. They are directives, commissives, expressives, and declaratives. The researcher also finds the act of the speakers, they are requesting, information, questioning, complimenting, promising, loving, and anger.